Trade Openness and Manufacturing Sector Growth: An Empirical Analysis for Nigeria - Onakoya, Adegbemi B.O; Fasanya, Ismail O.; Babalola, Muhibat T. (Mediterranean Journal of Social Sciences, 2012)
This study examines the impact of trade openness on manufacturing sector performance in the Nigerian economy,using a time series data from 1975 to 2010. The effects of stochastic shocks of each of the endogenous variables are exploredusing Error Correction Model (ECM). The analysis shows that trade openness has a positive impact on the manufacturing sectorperformance while exchange rate, inflation rate have a negative impact on the sector performance. The error correctioncoefficient also indicates rate of adjustment for disequilibrium of the variables shows that growth in the manufacturing sectoradjust slowly in the economy. The development of Manufacturing sector and its effective promotion have not been approachedseriously in Nigeria, hence, the lack of their impact in the economy. This could be attributed to a plethora of factors, including aweak technological base and low level of capacity utilization. Another major finding from this study is that there are significantpay-offs from the policy of trade liberalization. This study therefore recommends that government should avoid short-term fixesand front-loaded deals with other countries and move beyond arrangements that focus solely on the petroleum sector. Also topromote the imports of capital goods, there the need for transparent oversight largely monitored by regulatory institutions.